Determinants of FDI inflow in Asia / Anita Hasli, Catherine S F Ho and Nurhani Aba Ibrahim. - Hasli, Anita; Ho, Catherine S F; Ibrahim, Nurhani Aba (Universiti Teknologi Mara Selangor, 2015)
The research analyses the determinants of FDI inflow in Asia for the period 1993-2013 and is based on the fixed effect model. The macroeconomic factors included are lending rate, GDP per capita, trade openness, debt, exchange rate, money supply and unemployment rate. The country specific factors included are adult literacy rate, gross fixed capital formation, domestic credit provided by the financial sector, environmental pollution and natural resources rents. The study applies panel unit root tests, panel cointegration analysis and panel regression analysis based on the fixed effect model to ascertain the significance of macroeconomic and country specific factors on FDI inflow in Asia. The study found that lending rate, trade openness and money supply have a positive significance to FDI per capita whereas debt, unemployment rate and environmental pollution have a negative significance to FDI per capita.